Hospitalidade. turismo e desenvolvimento turístico : construção do perfil de uma comunidade como corpo coletivo acolhedor, sob a ótica de sujeitos primariamente acolhedores, numa perspectiva sociodinâmica relacional - Zerger, Evelise (My University, 2017)
In the context of the process of the tourist potentiality’s developement of a place, it is necessary to give voice and to listen to the community in order to create solid bases. The present study tried to elucidate the following question: Which features can show tourism and welcoming conceptions and the stablished relations between these phenomenon by the primarily welcoming subjects of Urupema/SC city, concerning to a construction of this community profile as a Welcoming Collective Group? Then this study set as objectives: to infer and to analyze the traces of these conceptions and relations; to provide a construction of subsidies in order to make this community recognized as a Welcoming Collective Group – WCG, in Santos, Perazzolo and Pereira (2014) definitions, and to its inhabitants can recognize the relational dynamic of this Group and recognize themselves; to point out subsidies to favor some actions, in order to promote the development of the welcoming competence. And contribute to the potentiation of the tourism development of the city taking into account the municipal and state public policy.Without considering the multiple analitic sides of the tourism and the welcoming, this study has as basic assumptions of reference the conceptual propositions of tourism by Perazzolo, Santos and Pereira (2013) which were constructed at the psycanalisis theories, specially with the Freud and Lacan’s contributions about the subject constitution as well as hospitality or welcoming which were comprehended as one of the tourism founding elements.The research is exploratory descriptive and has the qualitative character priority and developed methodological procedures which were defined by the hermeneutics approach of the data which were obtained by semi-structured interviews with 17 subjects of different segments that are considered as representative in Urupema’s community.The analysis and interpretation of the results were done by the Content Analysis (BARDIN, 2000) and complemented by the analysis of the Linguistics of Enunciation (FUCHS, 1985 and FLORES et al., 2009). The discursives detectors pointed out to a tourism conception underlying to the subject’s speech which is predominantly with marketing fields with emphasis to the structural and operational kinds linked to the offering and demanding of tourism products in order to the constitution of a touristic destination.This structural and services provision is derived from the prioritization of an instrumental pattern of the welcoming willingness (the welcomer as the environment, a mechanism to attend supposed internal and self-centered dermands of the tourist/guest) our tourism conceptual references typologies were developed by Perazzolo, Santos and Ferreira (2016) and related to the welcoming of the willingness in the hospitality’s construction.In terms of the features that delineate the Urupema’s community profile as WCG, it was not identified by the primary welcoming subjects, a direct and sufficient comprehension, and consequent implementation of the systemic relations, inherent to the model, among services, management and culture, undermining the linkages among them.In this sense, we propose something beyond training or professional qualification, the planning and development of some collective reflexive actions which can favor tourism and welcoming conceptual resignifications and of the related relations on the part of the primary welcoming subjects which would make known on the strengthening of the sense of belonging to this community and then to reflect at the tourism and welcoming daily practicing.
No contexto do processo de desenvolvimento da potencialidade turística de uma localidade, faz-se fundamental dar voz e promover a escuta da comunidade, para assim alicerçar frutíferas bases. O presente trabalho, ao buscar responder à questão Que traços sinalizam concepções de turismo e hospitalidade/acolhimento e relações estabelecidas entre esses fenômenos, por parte de sujeitos primariamente acolhedores do município de Urupema/SC, que possam encaminhar à construção de um perfil dessa comunidade como Corpo Coletivo Acolhedor?, estabelece como objetivos: depreender e analisar sinalizadores dessas concepções e relações; propiciar a construção de subsídios para que uma comunidade seja reconhecida como um Corpo Coletivo Acolhedor – CCA, na definição de Santos, Perazzolo e Pereira (2014), e para que seus integrantes reconheçam a dinâmica relacional desse Corpo e nela se reconheçam; aportar subsídios para favorecer o desencadeamento de ações, no sentido de promover o desenvolvimento da competência para o acolhimento e, sob essa ótica, contribuir para a potencialização do desenvolvimento turístico do município, indo ao encontro das políticas públicas municipal e estadual. Sem desconsiderar as múltiplas vertentes analíticas do turismo e da hospitalidade, nesta investigação, tem-se como supostos básicos de referência, as proposições conceituais de turismo, de Perazzolo, Santos e Pereira (2013a), construídas no marco teórico da psicanálise, particularmente ao amparo de contribuições freudianas e lacanianas sobre a constituição do sujeito, bem como de hospitalidade, ou acolhimento, entendidos como um dos elementos fundantes do turismo. A pesquisa, de natureza exploratório-descritiva, tem caráter prioritariamente qualitativo e desenvolve procedimentos metodológicos definidos a partir de uma abordagem hermenêutica dos dados, cuja obtenção resultou de entrevistas semiestruturadas junto a 17 sujeitos de diferentes segmentos considerados representativos da comunidade Urupema. A análise e interpretação dos dados deu-se por meio de aproximações à técnica de Análise de Conteúdo (BARDIN, 2000), complementadas por análises linguístico-enunciativas (FUCHS, 1985 e FLORES et al., 2009). Os sinalizadores discursivos apontam para uma concepção de turismo subjacente ao discurso dos sujeitos, predominantemente mercadológica, com ênfase aos elementos de ordem estrutural e operacional vinculados à oferta e demanda de produtos turísticos com vistas à constituição de um destino turístico. Essa disponibilização de estruturas e serviços deriva da priorização de um padrão instrumental de disposição para o acolhimento (o acolhedor como meio, instrumento para atender a supostas demandas intrínsecas e autocentradas do turista/visitante), tendo por referência conceitual tipologias de turismo tecidas por Perazzolo, Santos e Ferreira (2016, no prelo), relacionadas ao acolhimento do desejo na construção da hospitalidade. No que tange aos traços que delineiam o perfil da comunidade Urupema como CCA, não se identifica, por parte dos sujeitos primariamente acolhedores, clara e suficiente compreensão – e consequente implementação - das relações sistêmicas, inerentes ao modelo, entre serviços, gestão e cultura, fragilizando os elos entre eles. Nesse sentido propõe-se, para além de treinamentos ou atividades de qualificação técnica, o planejamento e desenvolvimento de ações reflexivas coletivas que favoreçam ressignificações conceituais de turismo, hospitalidade/acolhimento e das respectivas relações por parte dos sujeitos primariamente acolhedores, que repercutam no fortalecimento do sentimento de pertencimento a essa comunidade, o qual, por sua vez, se reflita nas práticas cotidianas de turismo e hospitalidade/acolhimento.
Keywords: Turismo - Urupema (SC); Turismo - Aspectos sociais; Hospitalidade; Tourist trade - Urupema (Brazil); Tourist trade - Social aspects; Hospitality